주요 국산수종의 휨가공성 평가 - 정인석; In Suk Jung; 이원희; Weon Hee Lee; 장준복; Jun Pok Chang; 배현미; Hyun Mi Bae (목재공학, 2002)
This study was carried out to evaluate bending property on principal domestic species such as sargent cherry(Prunus sargentii), bitter wood(Picrasma quassioides), horn beam(Carpinus laxiflora), cork oak(Quercus variabilis), birch(Betula schmidtii), painted maple(Acer mono), basswood(Tilia amurensis), red pine(Pinus densiflora), pitch pine(Pinus rigtda), royal pawlonia(Paulownia tomentosa) by microwave heating. In this study, radius of curvature(ROC) for bending process was classified by radius of curvature(ROC) of bending plate such as 4 cm, 6 cm, and 10 cm, and thickness of metal-strap(TMS) was 0.6 mm and 0.8 mm. Bending process was successfully operated for 100 percent in bitter wood, horn beam, birch and painted maple. On the other hand, there was a success rate of 58 percent in sargent cherry and 83 percent in cork oak and 29 percent in basswood and 8 percent in royal pawlonia which is the worst bending property. All specimens of basswood and royal pawlonia were broken at 4 cm of ROC. Success rate of bending property was shown 44 percent in red pine and 56 percent in pitch pine. TMS has an effect on only drying speed in drying process than difficulty and facility of bending property. It was considered that the thinner TMS in drying process is the faster in drying speed of bent wood. 본 연구는 고주파 가열에 의한 산벚나무, 소태나무, 서어나무, 굴참나무, 박달나무, 고로쇠나무, 피나무, 소나무, 리기다 소나무, 참오동나무의 휨가공성을 평가해 보기 위하여 실시하였다. 본 연구에서 휨가공을 위한 곡율반경은 휨틀의 곡율반경에 의해 4 cm, 6 cm, 10 cm으로 구분하고, 대철의 두께는 0.6 mm와 0.8 mm로 구분하였다. 본 연구결과 소태나무, 서어나무, 박달나무, 고로쇠나무는 모든 곡율반경에서 100% 성공률을 나타내었다. 산벚나무와 굴참나무의 경우 58%와 83%의 성공률을 각각 나타내었다. 피나무와 오동나무의 경우 총 29%와 8%로 매우 불량하게 나타났고, 곡율반경 4 cm에서는 모두 실패로 나타났다. 침엽수재인 소나무와 리기다 소나무는 각각 44%와 56%의 성공률을 나타내었다. 대철의 두께는 휨가공성의 쉽고 어려움보다는 건조시 건조속도에 더 많은 영향을 주는 것으로 나타났다. 건조과정에서 대철두께가 얇을수록 휨가공부재의 건조 속도가 빠른 경향을 나타내었다.